Molecular and Physiological Characterization of Fluoroquinolone-Highly Resistant Salmonella Enteritidis Strains - Vidovic, Sinisa; An, Ran; Rendahl, Aaron (Frontiers in Microbiology, 2019)
Four clinical isolates of Salmonella Enteritidis, susceptible to ciprofloxacin, and their spontaneous ciprofloxacin resistant (MICs from 8 to 16 μg/mL) and highly resistant (MIC 2048 μg/mL) mutants were used to gain an insight into the dynamics of development of fluoroquinolone (FQs) resistance in S. Enteritidis serovar. The first two high-frequency (i.e., mutations that occurred in each tested strain) mutations occurred in the gyrA, resulting in amino acid substitutions S83Y and S83F as well as D87G. Amino acid substitution D87G was significantly associated with the highly resistant mutants. Another high-frequency mutation, deletion in the ramRA intergenic region, was determined among the same group of highly resistant mutants. More importantly, each of these deletion mutations affected the RamR binding site. The effect of one 41 bp deletion mutation was empirically tested. The results showed that the deletion was responsible for resistance to ceftiofur and amoxicillin/clavulanic acid and decreased susceptibility to azithromycin and tetracycline. Performing gene expression assays across all ciprofloxacin susceptible groups, we found a consistent and significant upregulation of the ramA, acrB, and tolC (efflux pump associated genes) and downregulation of ompF (porin), clearly illustrating the importance of not only efflux but also porin-mediated permeability in the development of FQs resistance. Our data also showed that S. Enteritidis could acquire multiple mutations in QRDR region, further resulting in no up regulation of the ramA, acrB and tolC genes. These QRDR mutations and no activation of the AcrAB efflux pump seem to preserve the fitness of this organism compared to the S. Enteritidis strains that did not acquire multiple QRDR mutations. This report describes the dynamics of FQ-associated mutations in the highly resistant in FQ mutants in S. Enteritidis. In addition, we characterized a deletion in the ramRA integenic region, demonstrating that this frequent mutation in the highly resistant FQ mutants provide resistance or reduce susceptibility to multiple families of antibiotics.